AB0668 Use of Nonsteroidal Antiinflammatory Drugs in Patients with Axial Spondyloarthritis. (10th June 2014) - Aparicio, M.; Ricse, M.; Albert, G.; Heredia, S.; Zacarias, A.; Borrell, H.; Armengol, E.; Rodríguez-Moreno, J.; Nolla, J.M.; Juanola, X.
Abstract : Objectives: To assess the use of nonsteroidal antiinflammatory drugs (NSAIDs) in patients with axial spondyloarthritis (SpA) and their relationship with clinical, analytical and radiographic variables and biologic drugs (BD). Methods: All patients with SpA axial ASAS criteria included in a prospectively designed database has been reviewed. To assess the use of NSAIDs, the information of the last visit included in the database has been collected. Patients have been categorized according to the NSAIDs dose administered in the last 3 months, in the following groups: 1) No NSAID: no intake, 2) NSAID minimum dose: <25% optimal symptomatic dose, 3) NSAID medium dose: between 25-75% of optimal symptomatic dose and 4) NSAID high dose: >75% of optimal symptomatic dose. We dichotomised patients into Group A (No NSAIDs or minimum dose) and Group B (medium or high dose). The following variables were recorded: filiation data, diagnosis, time of evolution, HLA B27, CRP, ESR, BASDAI, BASFI, ASDAS, BASRI, biological disease modifying drugs, history of hypertension, previous peptic ulcers, dose and type of NSAID. A descriptive analysis was developed using percentages, means and standard deviation. Statistical tests used were: Fisher test, independent Student T, Mantel-Haenszel and Mann-Whitney test. Results: 294 patients with axial SpA were included: 74.8% male, mean age 53.8 (±14) years, age of onset 26.5 (±9) years, duration of the disease 27.3 (±14) years, 83.7% positive for HLA-B27 antigen, 89.8% did meet criteria for ankylosing spondylitis, CRP 5.9 (±8) mg/L, ESR 9.6 (±9.6), BASDAI 3.6 (±2.2), BASFI 3.6 (±2.5), ASDAS-CRP 2.1 (±1), ASDAS-ESR 2 (±0.9), sacroiliac BASRI 3.1, axial BASRI 6. 36.4% had history of hypertension and 4.6% previous peptic ulcers, 26.9% taking BD. The NSAID that was most frequently prescribed was etoricoxib (34.5%), followed by indomethacin (21.6%) and diclofenac/aceclofenac (18.7%). Of the total sample, 158 were Group A (54.5%) and 132 (45.5%) Group B. Group B has been associated with higher scores of BASDAI, ASDAS, CRP and ESR with a statistically significant difference (p<0.01). The Group A has been associated with older age (p=0.01), longer history of the disease (p<0.01) and previous peptic ulcers (p=0.02). Conclusions: – Most patients with axial SpA do not take any NSAIDs or does it at low doses. – Older patients, with greater radiographic damage or longer history take less NSAIDs. – Taking NSAIDs has been associated with rates of activity. – Etoricoxib is the most currently used. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4732